1971
DOI: 10.1139/y71-020
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Effect Relationship in Desoxycorticosterone Hypertension : Reduced Sensitivity in Adrenalectomized Rats and Its Possible Significance to the Etiology of Adrenal-Regeneration Hypertension

Abstract: Experiments were conducted to determine the smallest dose of DOCA which would cause saline polydipsia and induce hypertensive disease in unilaterally nephrectomized rats. This was found to be about 25 μg/day with the dosages used. This dose, and one five times as great, were then used to compare the sensitivity of adrenalectomized rats with that of animals having intact adrenals. Completely adrenalectomized animals were less responsive to the blood pressure effect at either dosage, whereas animals with regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In contrast, administration of DOCA at a dose of 125 pg (0.34 pmol)/day in oil to the Sprague-Dawley rat predictably produces hypertension (Hall & Ayachi, 1971). The Long-Evans rat does not exhibit saline polydipsia during mineralocorticoid administration, which is characteristic of other rat strains (Hall & Ayachi, 1971), but does develop hypokalaemia (Hall et al, 1972) and a fall in renal renin concentration (Park,197 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, administration of DOCA at a dose of 125 pg (0.34 pmol)/day in oil to the Sprague-Dawley rat predictably produces hypertension (Hall & Ayachi, 1971). The Long-Evans rat does not exhibit saline polydipsia during mineralocorticoid administration, which is characteristic of other rat strains (Hall & Ayachi, 1971), but does develop hypokalaemia (Hall et al, 1972) and a fall in renal renin concentration (Park,197 1).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, administration of DOCA at a dose of 125 pg (0.34 pmol)/day in oil to the Sprague-Dawley rat predictably produces hypertension (Hall & Ayachi, 1971). The Long-Evans rat does not exhibit saline polydipsia during mineralocorticoid administration, which is characteristic of other rat strains (Hall & Ayachi, 1971), but does develop hypokalaemia (Hall et al, 1972) and a fall in renal renin concentration (Park,197 1). A hypothalamic receptor for DOCA, which has been postulated to initiate the saline polydipsia, has been reported to be deficient in the Long-Evans rat, suggesting that this deficiency provides resistance to DOCA hypertension (Lassman & Mulrow, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators (7-9) have found elevated serum concentrations of deoxycorticosterone (DOC; 21-hydroxy-4-pregnene-3,20-dione) and attribute the hypertension to this finding. However, others (4) have contended that DOC excess does not satisfactorily explain ARH, since administration of DOC uniformly produces overt hypokalemia (10) and striking saline polydipsia (11), two features which are not characteristic of ARH (4). Excessive production of other known mineralocorticoids has not been found.…”
mentioning
confidence: 99%